Conchostráceos Palaeolimnadiopsis (Spinicaudata, Crustacea) do grupo Bauru (cretáceo superior, bacia Bauru): Taxonomia, paleoecologia e paleobiogeografia - Augusto Carbonaro, Fábio [UNESP]; Rohn, Rosemarie [UNESP]; Pirani Ghilardi, Renato [UNESP] (Sociedade Brasileira de Paleontologia, 2013)
The present study presents a taxonomic review of Palaeolimnadiopsis suarezi Mezzalira described in Bauru Group. The geographic and stratigraphic distribution of the genus Palaeolimnadiopsis is widespread, including occurrences in several countries as Brazil, Bolivia, Chile, Uruguay, USA, Congo, China, Australia, Tasmania, Russia, Germany, Scottland, France and Belgium, in rocks from the Devonian to the Cretaceous. This taxon was probably eurytopic, with a high dispersal potential and very conservative in evolution. One specimen identified as Palaeolimnadiopsis sp. is much larger than the average (~3.5 cm long), presenting relatively wide and few growth bands. The gigantism of this specie may be related to conditions that excluded potential predators and competitors from the environment, as is indicated by the presence of more saline and/or alkaline water conditions than in normal fresh water suggested a relatively high proportion of carbonates in that region and stratigraphic interval. © 2013 by the Sociedade Brasileira de Paleontologia.
Palaeolimnadiopsis conchostracans (Spinicaudata, Crustacea) from Bauru Group (Upper Cretaceous, Bauru basin): Taxonomy, paleoecology and paleobiogeography
Keywords: Bauru basin; Conchostraca; Giantism